2008
DOI: 10.1177/1077801207312633
|View full text |Cite
|
Sign up to set email alerts
|

Findings From an Outcome Examination of Rhode Island's Specialized Domestic Violence Probation Supervision Program

Abstract: An examination of specialized domestic violence probation supervision compared to traditional mixed case supervision of domestic violence probationers finds significant differences in several areas, including victim satisfaction, probationer accountability, and reabuse and rearrest rates. Lower-risk abusers, constituting almost half of the probation abuser caseload supervised by the specialized unit, were significantly less likely to be rearrested for domestic violence and nondomestic violence crimes than were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…There is substantial evidence that a significant percentage of male perpetrators of IPV have borderline personality tendencies with accompanying affect regulation difficulties as noted earlier on in this article. As a result, interventions such as dialectical behavior therapy, which have demonstrated effectiveness with people with borderline personality disorder (Kliem, Kröger, & Kosfelder, 2010), has been proposed as a treatment strategy for those male perpetrators of IPV with the aforementioned characteristics (Cavanaugh, Solomon, & Gelles, 2011;Fruzzetti & Levensky, 2000;Tollefson, Webb, Shumway, Block, & Nakamura, 2009). Cavanaugh et al (2011) presented the findings of a randomized controlled trial (RCT) of an experimental intervention (Dialectical Psychoeducational Workshop [DPEW]) and a control condition, an 8-week anger management program (AMW) providing preliminary support for the DPEW's effectiveness in lowering a participant's desire to express anger physically while decreasing the potential risk for physical violence.…”
Section: Resultsmentioning
confidence: 99%
“…There is substantial evidence that a significant percentage of male perpetrators of IPV have borderline personality tendencies with accompanying affect regulation difficulties as noted earlier on in this article. As a result, interventions such as dialectical behavior therapy, which have demonstrated effectiveness with people with borderline personality disorder (Kliem, Kröger, & Kosfelder, 2010), has been proposed as a treatment strategy for those male perpetrators of IPV with the aforementioned characteristics (Cavanaugh, Solomon, & Gelles, 2011;Fruzzetti & Levensky, 2000;Tollefson, Webb, Shumway, Block, & Nakamura, 2009). Cavanaugh et al (2011) presented the findings of a randomized controlled trial (RCT) of an experimental intervention (Dialectical Psychoeducational Workshop [DPEW]) and a control condition, an 8-week anger management program (AMW) providing preliminary support for the DPEW's effectiveness in lowering a participant's desire to express anger physically while decreasing the potential risk for physical violence.…”
Section: Resultsmentioning
confidence: 99%
“…However, increasing public awareness and concern for domestic assault may result in increased reporting by neighbors or other bystanders (Cassidy, Nichol, Ross & Lonsway, 2004;Robinson & Chandek, 2000). For example, Klein (2006) reported that the vast majority of calls to the police for domestic assault in the State of Rhode Island did not come from the victim. The involvement of an external complainant may have increased officers' perceived need to "do something" to resolve the incident.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the study found that specialized supervision of abusers reduced reabuse as measured by rearrest for up to 1 year for lowerrisk probationers. Such lower-risk probationers consisted of about half of the domestic violence probation caseload across the state (Klein & Crowe, 2008).…”
Section: Other Domestic Violence Interventions That Also Claim Successmentioning
confidence: 99%